2022
DOI: 10.1002/acn3.51570
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of neurologic symptoms in non‐hospitalized COVID‐19 “long haulers”

Abstract: Objective We characterized the evolution of neurologic symptoms and self‐perceived recovery of non‐hospitalized COVID‐19 “long haulers” 6–9 months after their initial Neuro‐COVID‐19 clinic evaluation. Methods In this follow‐up study on the first 100 patients, 50 SARS‐CoV‐2 laboratory‐positive (SARS‐CoV‐2 + ), and 50 laboratory‐negative (SARS‐CoV‐2 − ), evaluated at our Neuro‐COVID‐19 clinic between May and November 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 48 publications
5
52
0
Order By: Relevance
“…Around 13% of all COVID-19 survivors have persistent fatigue at 6 months [143]. In our Neuro-COVID-19 clinic, 85% of non-hospitalized Neuro-PASC patients complained of fatigue [61], which persisted an average of 14.8 months after COVID-19 symptoms onset in a follow-up study [151].…”
Section: Epidemiology and Presentationmentioning
confidence: 84%
See 1 more Smart Citation
“…Around 13% of all COVID-19 survivors have persistent fatigue at 6 months [143]. In our Neuro-COVID-19 clinic, 85% of non-hospitalized Neuro-PASC patients complained of fatigue [61], which persisted an average of 14.8 months after COVID-19 symptoms onset in a follow-up study [151].…”
Section: Epidemiology and Presentationmentioning
confidence: 84%
“…The main neurologic manifestations were "brain fog" (81%), headache (68%), numbness/tingling (60%), dysgeusia (59%), and anosmia (55%). In a follow-up study, there was no significant change in the frequency of most neurologic symptoms at a median of 14.8 months from disease onset [151].…”
Section: Neurologic Manifestations Of Post-acute Sequelae Of Sars-cov...mentioning
confidence: 87%
“…The mechanism through which auditory and vestibular symptoms could be provoked by COVID-19 remains unclear; proposed mechanisms include vestibular (or vestibulocochlear) neuritis; direct infection of cochlear and/or vestibular hair cells; labyrinthine ischemia; intralabyrinthine hemorrhage; and autonomic dysfunction. The pandemic has lasted long enough for investigators to begin to recognize "long-haul" COVID-19 symptoms, often defined as symptoms persisting >6 months beyond initial infection; a recent study of such patients reported that symptoms such as dizziness and tinnitus, if present at the initial evaluation, were either still present or had actually increased by the time of the followup evaluation at 6-9 months [49].…”
Section: Discussionmentioning
confidence: 99%
“…A smaller but growing literature is also beginning to document an association between COVID-19 and tinnitus [36,37,39,44,45,[48][49][50][51][52][53]. In many cases, the tinnitus accompanies hearing loss [36,37,39].…”
Section: Covid-19 Associated With Auditory Disordersmentioning
confidence: 99%
“…Gastrointestinal symptoms with, for instance, signs of colitis at computed tomography (e.g., bowel wall thickening) [9,12], anosmia expressed as olfactory bulb anomalies at MR [10,13] or myocarditis-like features (e.g., myocardial edema and/or late gadolinium enhancement) at cardiac MR in children with multisystem inflammatory syndrome (MIS-C) due to COVID-19 [11,14] are just some examples of disease manifestation which can be radiologically identified. Such a wide spectrum of symptoms may occur and also persist in the so called Post-COVID syndrome or Long-COVID that, as recently demonstrated, may last over a year [15]. In fact, patients may experience enduring pulmonary, cardiovascular, endocrine, hematologic, gastrointestinal, neurological, and/or psychiatric signs [16].…”
mentioning
confidence: 95%